Mineral resource estimation of alluvial Gold deposits - a comparative study - Engmann, Eric Walter (2012)
A thesis submitted to the Board of Postgraduate Studies, Kwame Nkrumah University of Science and Technology, Kumasi in partial fulfilment of the requirements for the Master of Science (MSc) Degree in Mineral Exploration.